Cultural sociability, journalism and mobilization in argentine socialism: The Casa del Pueblo of Buenos Aires, 1927-1953 (Estudios Sociales, 2018)
The article studies the history of the Casa del Pueblo, epicenter of the political and cultural sociability of the Socialist Party in the city of Buenos Aires during the 1930s and 1940s. One of the interests of the work is the crossing between political sociability and journalism, from the perspective offered by La Vanguardia, a party press organization whose workshops and editorial offices occupied a large part of the building. Likewise, the article examines the uses of the Casa del Pueblo in the context of the entanglement between political life and the mass culture characteristic of this period. To do this, it analyzes the cultural role played by the great socialist center, alternating and combining the modalities of the athenaeum, the popular university and the social club, and addresses the forms of mobilization and political use of the street that were deployed around the building.
Keywords: Socialism; Sociability; Journalism; Mobilization; Mass Culture